CAM and Pediatric Oncology: Where Are All the Best Cases?. (25th August 2013) - Adams, Denise; Spelliscy, Courtney; Sivakumar, Leka; Grundy, Paul; Leis, Anne; Sencer, Susan; Vohra, Sunita
Abstract : Background . Use of complementary and alternative medicine (CAM) by children with cancer is high; however, pediatric best cases are rare. Objectives . To investigate whether best cases exist in pediatric oncology using a three-phase approach and to compare our methods with other such programs. Methods . In phase I, Children's Oncology Group (COG) oncologists were approached via email and asked to recall patients who were (i) under 18 when diagnosed with cancer, (ii) diagnosed between 1990 and 2006, (iii) had unexpectedly positive clinical outcome, and (iv) reported using CAM during or after cancer treatment. Phase II involved partnering with CAM research networks; patients who were self-identified as best cases were asked to submit reports completed in conjunction with their oncologists. Phase III extended this partnership to 200 CAM associations and training organizations. Results . In phase I, ten cases from three COG sites were submitted, and most involved use of traditional Chinese medicine to improve quality of life. Phases II and III did not yield further cases. Conclusion . Identification of best cases has been suggested as an important step in guiding CAM research. The CARE Best Case Series Program had limited success in identifying pediatric cases despite the three approaches we used.